UJI KINERJA SILO PENGERING DARI ANYAMAN BAMBU UNTUK PROSES PENGERINGAN GABAH - , RIDHO ANDIKA PUTRA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Handling of agricultural products such as grains are generally still done by utilizing solar energy. However, this method is highly dependent on the season, drying time, a lot of labor, and the large place. Changes in the use of solar drying to a mechanical dryer is necessary for the drying process can be done better. However, the cost of construction and high operational equipment does not allow for farmers to use. Therefore, in this research, drying grains use a simple mechanical construction dryer so that the cost can be reached by farmers. In the wake of research done by designing a simple mechanical dryers. The main material used to make these dryers are gedheg which is formed from woven bamboo and wood are also used to frame reinforcement tool that does not fall when the seeds included. Then test these tools. The materials used for the test tool is then measured grain moisture content, temperature. Additionally it also measured the temperature and humidity environment and air velocity variation with bottom opening, opening up, and aperture combination. And the results showed that the combination of openings rate the greater the decrease in water content so that the variation is a combination of drying time for drying faster than the openings above and below openings.